Detailed dosimetry calculation for in-vitro experiments and its impact on clinical BNCT. (September 2021) - Viegas, Ana Mailén Dattoli; Postuma, Ian; Bortolussi, Silva; Guidi, Claretta; Riback, Jessica Sofía; Provenzano, Lucas; Marcaccio, Barbara; Rossini, Andrés Eugenio; Ferrari, Cinzia; Cansolino, Laura; Ferrari, Matteo; Portu, Agustina Mariana; et al.
Highlights: Determination of adequate dose calculation strategies for in-vitro BNCT experiments. Demonstration of the dose overestimation in cell cultures under CPE approximation. New parameters of photon iso-effective dose models for UMR-106 and Mel-J cells. Evidence of the significant impact of dose corrections on the RBE for neutrons. Evidence of the significant impact of dose corrections on the clinical BNCT. Abstract: Purpose: Boron Neutron Capture Therapy (BNCT) is a form of hadrontherapy based on the selective damage caused by the products of neutron capture in 10 B to tumour cells. BNCT dosimetry strongly depends on the parameters of the dose calculation models derived from radiobiological experiments. This works aims at determining an adequate dosimetry for in-vitro experiments involving irradiation of monolayer-cultured cells with photons and BNCT and assessing its impact on clinical settings. M&M: Dose calculations for rat osteosarcoma UMR-106 and human metastatic melanoma Mel-J cell survival experiments were performed using MCNP, transporting uncharged particles for KERMA determinations, and secondary particles (electrons, protons, 14 C, 4 He and 7 Li) to compute absorbed dose in cultures. Dose-survival curves were modified according to the dose correction factors determined from computational studies. New radiobiological parameters of the photon isoeffective dose models for osteosarcoma and metastatic melanoma tumours were obtained. Dosimetry implications considering cutaneous melanoma patients treated in Argentina with BNCT were assessed and discussed. Results: KERMA values for the monolayer-cultured cells overestimate absorbed doses of radiation components of interest in BNCT. Detailed dose calculations for the osteosarcoma irradiation increased the relative biological effectiveness factor RBE1% of the neutron component in more than 30%. The analysis based on melanoma cases reveals that the use of survival curves based on KERMA leads to an underestimation of the tumour doses delivered to patients. Conclusions: Considering detailed dose calculation for in-vitro experiments significantly impact on the prediction of the tumor control in patients. Therefore, proposed methods are clinically relevant.